Soil nitrogen and phosphorus depletion as a means of restoring degraded lowland fynbos ecosystems invaded by alien grasses - Ruwanza, Sheunesu (Stellenbosch : Stellenbosch University, 2009)
Thesis (MSc (Conservation Ecology and Entomology))--University of Stellenbosch, 2009.